Healthcare law and ethics and the challenges of public policy making : selected essays - Kennedy, Ian, 1941- (London, England : Zed Books, 2021)
"Drawing on Sir Ian Kennedy's extensive experience in healthcare law, ethics and public policy-making, this book explores vital issues in the law surrounding healthcare and regulation. The book contains a range of published and unpublished essays and speeches with the addition of notes and commentaries by the author that bring the pieces up to the present day. Those who want to understand developments, from transplants to confidentiality, from COVID-19 to public inquiries to regulation will find a rich seam of rigorous, informed analysis. The author's unique range of experience allows him to share insights on a variety of issues; from the conduct of the disgraced breast surgeon, Ian Paterson, to research at Porton Down, to the economics of innovation in drug development at NICE. His abiding interest in the welfare of children informs his trenchant forensic examination of how children fare in the NHS. Those involved in or with an interest in law, moral philosophy, and public policy will find much food for thought"--
Introduction -- Caring about children -- who cares? -- Getting it right for children and young people : overcoming cultural barriers in the NHS so as to meet their needs -- CHAI -- making it better -- The healthcare commission's blueprint for regulation -- The safety of healthcare : the role of regulation -- Value for money, who says? : the independent parliamentary standards authority : a case study -- Huntington's disease and confidentiality -- Reflections on Charlie Gard -- Doing what's best, who says? -- Ethical issues in transplantation -- A collection of children's hearts -- Safety and blame : learning from mistakes in the NHS -- Deprivation of liberty and medical care -- Rights and values in health and healthcare -- Sumption's gambit : give me liberty and give me death -- Public inquiries : experience from the Bristol public inquiry -- The Paterson review -- Inquiries in the NHS : what's the point? -- Appraising the value of innovation : a review for NICE -- Research at porton down : an ethical assessment -- Meet the press -- Working with the media : a view from the frontline -- Professor Aidan Halligan -- Sir Donald Irvine -- Sir Eric Scowen.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Medical care -- Law and legislation -- Great Britain; Medical policy -- Great Britain; Medical ethics -- Great Britain; Medical & healthcare law; Electronic books